Romero Britto e a publicidade: o contrato comunicacional das marcas e o consumo das padronagens - Okada, Miedja Ayumi Pina da Cunha (2010)
The present work analyses how Romero Britto build his brand, from the perspective that he is grounded in the Pop Art and transposes into a successful formula with the public galleries and with consumers of brand and products advertising. We are interested in investigating the production of Britto diachronic axis, analyzing the invariable elements in pop composition advertising that are used in advertising as in the artistic work to build a brand identity. The research problem is therefore how Romero Britto builds the semblance of doing artist to do advertising? Which the figurative elements contained in the composition and intertextual pop that while reiteration, are selected by the sender to be used in advertising and marketing strategies of other brands, besides brand? Taking into consideration the hypothesis that enunciatees make of the choices of consume from the universe of values built and gathered by theses brands, that is possible to verify the contexts of art and the publicity are going to interdiscourse ans intersemiotize, in Britto`s case. The verification of this hypothesis was tested the discoursive semiotics theory with its methodology of description and analysis of the elements while means of expression and content and the ways that these two forms are confirmed either through symbolic or semi-symbolic or motivated relations. The corpus of this research is located in six published books with the plastic art of Britto, as well as in the news and printed advertisement material, given by the artist's press release. The indention is made since 1989, when Romero Britto started to be known, until December 2009, a period in which we obtained a view about the Professional route by the artist inside the publicity and marketing spaces. Featuring the work of the theoretical A. J. Greimas and his collaborators to subsidize the production of semiotic analysis to make sense of Britto`s do. Among the contributors: Jean-Marie Floch whose ideas were used to study the messages of the level of expression in the advertising field; Eric Landowski, for the sensitive understanding of the images in the world and the systems of meaning that they produce in the interaction schemes; and Ana Claudia de Oliveira, for the analysis of intertextual territory and their sensibility qualities, operated through the mechanisms of enunciation actorality, spaceality temporality. In conclusion, on one hand the sender-brand makes its choices based on an artistic already acknowledged by the general public, and on the other hand, the sender-Britto falls within marketing to build its own brand as an artistic and advertising and obtain recognition of the consumer. Thus, this relation is presented as a naturalized state of the art world, that the consumer assumes to be an integral part of his social world. The research therefore found that the patterns of Britto are constructed from plastic and reiterations of his figurative art and are present in advertisements, packaging and products. Futhermore, these patterns also result in a marketing strategy of the artist, who wants to be seen and, the other brands that wish to always renew their modes of address and conquer the consuming public